Motifs in the permeation pathway of connexin channels mediate voltage and Ca2+ sensing - Harris, Andrew L.; Contreras, Jorge E. (Frontiers in Physiology, 2014)
Connexin channels mediate electrical coupling, intercellular molecular signaling and extracellular release of signaling molecules. Connexin proteins assemble intracellularly as hexamers to form plasma membrane hemichannels. The docking of two hemichannels in apposed cells forms a gap junction channel that allows direct electrical and selective cytoplasmic communication between adjacent cells. Hemichannels and junctional channels are gated by voltage, but extracellular Ca2+ also gates unpaired plasma membrane hemichannels. Unlike other ion channels, connexin channels do not contain discrete voltage- or Ca2+–sensing modules linked to a separate pore-forming module. All studies to date indicate that voltage and Ca2+ sensing are predominantly mediated by motifs that lie within or are exposed to the pore lumen. The sensors appear to be integral components of the gates, imposing an obligatory structural linkage between sensing and gating not commonly present in other ion channels, in which the sensors are semi-independent domains distinct from the pore. Because of this, the structural and electrostatic features that define connexin channel gating also define pore permeability properties, and vice versa; analysis/mutagenesis of gating and of permeability properties are linked. This offers unique challenges and opportunities for elucidating mechanisms of ligand and voltage-driven gating.